José Honório Rodrigues e a historiografia brasileira: em defesa de uma concepção de história - Oliveira, Krisley Aparecida de (2019)
José Honório Rodrigues is considered by many researchers who are dedicated to the study of Brazilian historical processes one of the pioneer intellectuals and "father of Brazilian historiography", having thought and produced since the 1940s themes concerning historiography as well as the office of the historian. The purpose of this study to investigate the conception of Rodrigues' history (1937-1987) with emphasis on the problems that it points in Brazilian history and their struggle for representation of history in the academic setting and in everyday life. Therefore, the intention is to go through his main books and texts, mapping his national and international professional training and performance and his intellectual journey, intersecting with authors, ideas and works from different places with which he maintained dialogue in an attempt to rework the plots and tensions throughout his writing that crossed a large and significant period of brazilian history, with political and social events decisive for the reasoning of his theses.